Décomposition et recomposition : présence et absence des corps noyés dans Lélia (1833) de George Sand et L’Éducation sentimentale (1845) de Gustave Flaubert - Carrico, Abbey (Quêtes littéraires, 2012)
In Romantic literature, water often serves as a symbol of death and of the dissolution of the individual, representing a passage from presence to absence. In order to show this transformation, writers frequently rely on scenes of drowning. However, in these depictions drowning does not always lead to an absence, but rather, it reveals a physical presence: that of the cadavers themselves. Through a detailed analysis of two romantic texts whose treatment of drowning sheds light on the relationship between absence and presence, Lélia (1833) by George Sand and L’Éducation sentimentale (1845) by Gustave Flaubert, this study engages the following questions on thematic and structural levels: Does drowning undeniably bring about an annihilation of the individual? Are the boundaries between absence and presence, disappearing and (re)appearing, decomposition and (re)composition, clearly defined? Or is there another interpretation? One that is specific to textual portrayals of immersion? From an eco-critical perspective, it is clear that water represents an ideal space to portray the tension between life and death. As presented by Sand and Flaubert, drowned bodies inspire images of life rather than death and therefore cause the reader to question these boundaries on an imaginative and symbolic level.